Long-segment pulmonary artery resection to avoid pneumonectomy: long-term results after prosthetic replacement. (28th September 2017) - D'Andrilli, Antonio; Maurizi, Giulio; Ciccone, Anna Maria; Andreetti, Claudio; Ibrahim, Mohsen; Menna, Cecilia; Vanni, Camilla; Venuta, Federico; Rendina, Erino A
Abstract: OBJECTIVES: Resection of a long pulmonary artery (PA) segment infiltrated by tumour and reconstruction by conduit interposition or wide patch is a challenging but feasible option to avoid pneumonectomy. Our goal was to report the long-term results of our experience with this type of operation using various techniques and materials. METHODS: Between 1991 and 2015, 24 patients underwent sleeve resection of a long PA segment or extended resection (>2.5 cm) of 1 aspect of the circumference of the PA associated with lobectomy for centrally located lung cancer. Materials used for conduit reconstruction (20 patients) included pulmonary vein in 12 patients, autologous pericardium in 4, porcine pericardium in 3 and bovine pericardium in 1. Patches used in 4 patients consisted of porcine pericardium (2 patients) and pulmonary vein (2 patients). RESULTS: Twenty-three patients underwent left upper lobectomy without associated bronchoplasty. One patient underwent bronchovascular left upper sleeve lobectomy. The postoperative morbidity rate was 29.1%. No complications related to the reconstructive procedure occurred. There were no postoperative deaths. Complete patency of the reconstructed PA was shown in all patients by postoperative contrast computed tomography performed every 6 months. Pathological tumour stage ranged from I to IIIA. Five-year overall survival and disease-free survival rates were 69.9% and 52.7%, respectively, at a median follow-up of 41 months. CONCLUSIONS: Resection of the long PA segment followed by conduit or wide patch reconstruction is a feasible, safe and effective option to avoid pneumonectomy. Different biological materials can be used to provide adequate tissue characteristics; the choice is made on a case-by-case basis. Long-term results confirm the oncological reliability of this operation.